Septic Embologenic Pneumonia — Clinical and Diagnostical Features (Review and Own Observations) - N. S. Chipigina; N. Yu. Karpova; A. S. Vinokurov; E. E. Arinina; Yu. A. Ivanova; A. A. Gasparyan; P. A. Kashkovskaya; A. G. Makaev; M. S. Sapko (Архивъ внутренней медицины, 2023)
In contrast to trivial bacterial pneumonia, the diagnosis of septic pulmonary embolism poses a fundamental task for the doctor to search for primary sources of emboli, including right side infective endocarditis, and to change the tactics of managing the patient accordingly. The similarity of the main clinical common and respiratory symptoms of septic pulmonary embolism with symptoms of other inflammatory processes in the lung makes their differential diagnosis difficult without the involvement of additional radiologic investigation methods. The review describes the special features of etiology and pathogenesis, as well as the clinic, complications and principles of diagnosis of septic embolic pneumonia.